Paradigms and Prospects of e-Assessment: A Scoping Review - Adhikari, Krishna Prasad; Joshi, Dirgha Raj; Sharma, Lekhnath (International Research Journal of MMC, 2025)
E-Learning is becoming more popular as a result of technological advancement. The focus of the e-learning environment is inclusivity and accessibility for all learners with diverse geographical and cognitive backgrounds, where students get the opportunity to learn at their own pace, place, and time. The growing adoption of e-learning in education is not only creating a new platform for teaching and learning but also raising the issues of e-assessment. Cooper's (1988) method of organizing knowledge synthesis was used in this study. This review paper is focused on concretizing the existing knowledge in the e-assessment based on the findings of the research articles. The article published from 2012 to 2024, focusing on the concept of e-assessment, strategies of e-assessment and issues in the implementation of e-assessment were included in this study. The review revealed three major findings related to e-assessment conception and perception, e-assessment of, for, and as learning, and issues of authentication and authorship in e-assessment. Based on the findings of the reviewed literature, it can be concluded that e-assessment could be a firm alternative to existing paper-based traditional assessment. The findings imply that effective implementation of e-assessment requires well-designed feedback-rich and learner-centered assessment practices supported by improved teacher competencies, inclusive digital infrastructure, and reliable measures to ensure authenticity and academic integrity.